Lactation performance of purebred Arsi cows and Friesian X Arsi crosses under pre-partum and post-partum supplementary feeding regimes - Kurtu, M.Y.; Tawah, C.L.; Rege, J.E.O.; Alemayehu, N.; Shibre, M. (Cambridge University Press, 1999)
A study was conducted at the Asella Station in the Arsi Region of Ethiopia to investigate the dairy performance of indigenous purebred Arsi and Friesian X Arsi crosses under different pre-partum and post-partum supplementary feeding regimes. A total of 343 first-lactation animals were involved in the experiment. Lactation performance was not significantly affected by pre-partum supplementation. Post-partum supplementary feeding significantly affected total lactation milk and butterfat yields of the crosses but not the purebred Arsi. Arsi crosses produced more milk (1873 (s.e. 65.1) 258 (s.e. 31.7) kg) and butterfat (92 (s.e. 4.0) 25 (s.e. 2.8) kg) than purebred Arsi. The crosses stayed in lactation longer (474 (s.e. 13.0) 179 (s.e. 15.4) days) than the latter. Purebred Arsi manifested much more variation in total lactation milk yield (CV: 1.27 0.37), lactation length (0.91 0.30) and butterfat yield (0.71 0.42) than Arsi crosses. F1 crosses produced slightly more milk (+266 kg) and butterfat (+19.3 kg) but had shorter (-30 days) lactations than the backcrosses.